2018
DOI: 10.1002/lary.27285
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age on Sinus Surgery Outcomes

Abstract: Objectives/Hypothesis To evaluate the impact of age on patient‐reported quality of life (QOL) following endoscopic sinus surgery (ESS) for chronic rhinosinusitis (CRS). Study Design Prospective cohort study. Methods Six hundred thirty‐six patients with CRS were recruited from 11 otolaryngologic practices and completed the sinonasal‐specific, 22‐item Sino‐Nasal Outcome Test‐22 (SNOT‐22) and general health‐related EuroQol 5‐Dimension (EQ‐5D) questionnaires at baseline and 12 and 24 months after ESS. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…Several previous studies have demonstrated that ESS offers an efficacious surgical treatment for the elderly patients with CRS. [5][6][7][8][9] Lehmann et al 8 and Yancey et al 9 compared age groups using well validated disease-specific quality of life (QOL) measurement (SNOT-22) and general health-related QOL and health utility value (HUV) instruments. They showed that young adults present with higher preoperative SNOT-22 score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have demonstrated that ESS offers an efficacious surgical treatment for the elderly patients with CRS. [5][6][7][8][9] Lehmann et al 8 and Yancey et al 9 compared age groups using well validated disease-specific quality of life (QOL) measurement (SNOT-22) and general health-related QOL and health utility value (HUV) instruments. They showed that young adults present with higher preoperative SNOT-22 score.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and efficacy of ESS for CRS has been well documented by numerous studies in the adult population. [5][6][7][8][9] Older adult patients may have an altered immune response and different morbidity profiles as compared to their younger adult counterparts. 10 Therefore, the severity of CRS at presentation may be different depending on the age of the patient, which in turn may affect treatment outcomes and ultimately subjective symptom scores.…”
Section: Introductionmentioning
confidence: 99%
“…It is a self-assessment of mobility, independence, activities of daily life, pain and anxiety/depression in 3 or 5 levels (EQ-5D-3L or -5L) as well as self-assessment of the health condition on a visual analogue scale. Improvements are found in the HRQoL of patients after sinus surgery in the EQ-5D, in particular in the subunits pain, anxiety/depression and activities of daily life [212,213].…”
Section: General Measures Of Health-related Quality Of Lifementioning
confidence: 99%
“…Довольно много исследований посвящено функциональному состоянию костной ткани различных локализаций: бедренной кости, поясничного отдела позвоночника [2]. Данные об изменении в губчатой кости стенок околоносовых синусов при физиологических процессах обрывочны, в то время как эта информация необходима для оценки патологических процессов данной локализации в связи со значительным удельным весом воспалительных процессов в ней [3], частотой хронизации этих процессов и неуемно растущим числом ослож нений. Так, к 2060 году прогнозируется двукратное увеличение удельного веса хронических риносинуситов среди пациентов старше 65 лет [3].…”
unclassified
“…Данные об изменении в губчатой кости стенок околоносовых синусов при физиологических процессах обрывочны, в то время как эта информация необходима для оценки патологических процессов данной локализации в связи со значительным удельным весом воспалительных процессов в ней [3], частотой хронизации этих процессов и неуемно растущим числом ослож нений. Так, к 2060 году прогнозируется двукратное увеличение удельного веса хронических риносинуситов среди пациентов старше 65 лет [3]. Не меньшую угрозу в себе несут и осложнения острых и хронических риносинуситов.…”
unclassified